Trophodynamics of the sclerosponge Ceratoporella nicholsoni along a shallow to mesophotic depth gradient - Keir J. Macartney; M. Sabrina Pankey; Marc Slattery; Michael P. Lesser (Coral Reefs, 2020)

A New “Business as Usual” Climate Scenario and the Stress Response of the Caribbean Coral Montastraea cavernosa - Michael P. Lesser; Jessica K. Jarett; Cara L. Fiore; Megan M. Thompson; M. Sabrina Pankey; Keir J. Macartney (Frontiers in Marine Science, 2020)

Depth‐dependent detritus production in the sponge, Halisarca caerulea - Michael P. Lesser; Benjamin Mueller; M. Sabrina Pankey; Keir J. Macartney; Marc Slattery; Jasper M. de Goeij (Limnology and Oceanography, 2020)
Sponges are important ecological and functional components of coral reefs. Recently, a new hypothesis about the functional ecology of sponges in organic matter recycling pathways, the sponge‐loop hypothesis, in which dissolved and particulate organic matter is taken up by sponges and shunted to higher trophic levels as detritus, has been proposed and demonstrated for shallow ( Halisarca caerulea from water depths of 10 and 50 m. Detritus production was significantly lower in mesophotic sponges compared to shallow samples of H. caerulea . Additionally, detritus production rates in transplanted sponges moved in the direction of rates observed for resident conspecifics. The microbiome of these sponge populations was also significantly different between shallow and mesophotic depths, and the microbial communities of the transplanted sponges also shifted in the direction of their new depth in 10 d largely driven by changes in Oxyphotobacteria , Acidimicrobiia , Nitrososphaeria , Nitrospira , Deltaproteobacteria , and Dadabacteriia . This occurred in an environment where the availability of both dissolved and particulate trophic resources changed significantly across the shallow to mesophotic depth gradient where these sponge populations were found. These results suggest that changes in sponge detritus production are primarily driven by differential quality and quantity of trophic resources, as well as their utilization by the sponge host, and its microbiome, along the shallow to mesophotic depth gradient.

Will coral reef sponges be winners in the Anthropocene? - Michael P. Lesser; Marc Slattery (Global Change Biology, 2020)
Recent observations have shown that increases in climate change‐related coral mortality cause changes in shallow coral reef community structure through phase shifts to alternative taxa. As a result, sponges have emerged as a potential candidate taxon to become a “winner,” and therefore a numerically and functionally dominant member of many coral reef communities. But, in order for this to occur, there must be sufficient trophic resources to support larger populations of these active filter‐feeding organisms. Globally, climate change is causing an increase in sea surface temperatures (SSTs) and a decrease in salinity, which can lead to an intensification in the stratification of shallow nearshore waters (0–200 m), that affects both the mixed layer depth (MLD) and the strength and duration of internal waves. Specifically, climate change‐driven increases in SSTs for tropical waters are predicted to cause increased stratification, and more stabilized surface waters. This causes a shallowing of the MLD which prevents nutrients from reaching the euphotic zone, and is predicted to decrease net primary production (NPP) up to 20% by the end of the century. Lower NPP would subsequently affect multiple trophic levels, including shallow benthic filter‐feeding communities, as the coupling between water column productivity and the benthos weakens. We argue here that sponge populations may actually be constrained, rather than promoted, by climate change due to decreases in their primary trophic resources, caused by bottom‐up forcing, secondary to physical changes in the water column (i.e., stratification and changes in the MLD resulting in lower nutrients and NPP). As a result, we predict sponge‐dominated tropical reefs will be rare, or short‐lived, if they occur at all into the future in the Anthropocene.